2016
DOI: 10.1080/17437199.2016.1172979
|View full text |Cite
|
Sign up to set email alerts
|

Self-directed interventions to promote weight loss: a systematic review and meta-analysis

Abstract: Downloaded by [2.124.227.49] at 11:47 19 April 2016 2 Many self-directed weight-loss interventions have been developed using a variety of delivery formats (e.g. internet, smartphone) and change techniques. Yet, little research has examined whether self-directed interventions can exclusively promote weight loss. MEDLINE, Embase, PsycINFO, CINAHL, and the Cochrane Library were systematically reviewed for randomised controlled trials evaluating self-directed interventions in relation to weight loss outcomes in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…More than 80 behaviour change theories (Davis, Campbell, Hildon, Hobbs, & Michie, 2015;Michie, West, Campbell, Brown, & Gainforth, 2014) and over 100 categories of change techniques (Abraham, 2016;Abraham & Michie, 2008;Michie et al, 2013) have been identified, some for specific intervention types including those targeting diet and physical activity (Michie, Churchill, & West, 2011), weight loss (Hartmann-Boyce, Aveyard, Koshiaris, & Jebb, 2016), smoking cessation (West, Walia, Hyder, Shahab, & Michie, 2010), and gambling problems (Rodda et al, 2018). Moreover, evidence on which types of techniques are associated with improved intervention effectiveness is accumulating (e.g., Dombrowski et al, 2012;Hartmann-Boyce, Johns, Jebb, & Aveyard, 2014;Michie, Abraham, Whittington, McAteer, & Gupta, 2009;Tang, Abraham, & Greaves, 2016). However, to date most research into change processes and change techniques has focused on individual-level, intra-personal change.…”
Section: Introductionmentioning
confidence: 99%
“…More than 80 behaviour change theories (Davis, Campbell, Hildon, Hobbs, & Michie, 2015;Michie, West, Campbell, Brown, & Gainforth, 2014) and over 100 categories of change techniques (Abraham, 2016;Abraham & Michie, 2008;Michie et al, 2013) have been identified, some for specific intervention types including those targeting diet and physical activity (Michie, Churchill, & West, 2011), weight loss (Hartmann-Boyce, Aveyard, Koshiaris, & Jebb, 2016), smoking cessation (West, Walia, Hyder, Shahab, & Michie, 2010), and gambling problems (Rodda et al, 2018). Moreover, evidence on which types of techniques are associated with improved intervention effectiveness is accumulating (e.g., Dombrowski et al, 2012;Hartmann-Boyce, Johns, Jebb, & Aveyard, 2014;Michie, Abraham, Whittington, McAteer, & Gupta, 2009;Tang, Abraham, & Greaves, 2016). However, to date most research into change processes and change techniques has focused on individual-level, intra-personal change.…”
Section: Introductionmentioning
confidence: 99%
“…The Internet is wellplaced to deliver self-directed interventions (i.e. those requiring no professional contact or simply an introductory face-to-face session [6]). If effective, self-directed interventions present a low-cost means of promoting healthy individual lifestyle change, requiring no or relatively less face-to-face time with specialist personnel [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent systematic reviews suggest that mobile apps are effective in promoting dietary self-regulation [7] and weight management [8][9][10][11][12][13][14]. Despite lacking evidence-based content [6,15], health apps can be used as standalone delivery modes in 'self-directed' weight loss interventions [16,17], or as supplemental components of complex interventions. Some studies employing researcher-developed apps [18] or popular calorie-counting apps (e.g., MyFitnessPal [19,20]) in combination with face-to-face delivery modes, showed generally larger effects compared to interventions using the apps as standalone [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Apps may include messages or notifications that remind users about their weight goals and provide positive feedback or reinforcements for achieving those goals. These features can trigger cognitive processes underpinning effective behavior change strategies or techniques [24][25][26][27][28][29], combining principles derived from selfdetermination theory [16,17] and persuasive technology [30,31]. In a recent review of 23 popular weight management apps [24], researchers found that most apps included several change techniques that are commonly employed in effective behavior change interventions.…”
Section: Introductionmentioning
confidence: 99%